Frontispiece: Aromaticity Relocation in Perylene Derivatives upon Two‐Electron Oxidation To Form Anthracene and Phenanthrene. Issue 41 (26th September 2016) - Matsumoto, Akinobu; Suzuki, Mitsuharu; Hayashi, Hironobu; Kuzuhara, Daiki; Yuasa, Junpei; Kawai, Tsuyoshi; Aratani, Naoki; Yamada, Hiroko
Abstract : Polycyclic Aromatic Hydrocarbons Radical cations and dications are not only important intermediates in organic transformations, but also crucial for a wide range of materials because of their intriguing electronic and optical properties. In their Communication onpage 14462 ff., N. Aratani and H. Yamada et al. prepared perylene dications by using "capped" perylene derivatives, and successfully obtained the single crystal of one of the perylene dication, for the first time. The experimental evidences proved that Clar′s aromatic π‐sextet rule can be applied even for the dicationic perylenes in a very simple way.